2022
DOI: 10.1186/s12864-022-08906-w
|View full text |Cite
|
Sign up to set email alerts
|

Genome-resolved analyses show an extensive diversification in key aerobic hydrocarbon-degrading enzymes across bacteria and archaea

Abstract: Background Hydrocarbons (HCs) are organic compounds composed solely of carbon and hydrogen that are mainly accumulated in oil reservoirs. As the introduction of all classes of hydrocarbons including crude oil and oil products into the environment has increased significantly, oil pollution has become a global ecological problem. However, our perception of pathways for biotic degradation of major HCs and key enzymes in these bioconversion processes has mainly been based on cultured microbes and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 107 publications
1
6
0
Order By: Relevance
“…In contrast, most microbes lack a complete set of enzymes. Instead, many microbes contain a subset for hydrocarbon degradation, an observation that is in agreement with findings in several previous studies [21][22][23][24] , suggesting that MDOL is prevalent in hydrocarbon degradation. When we assessed three degrading pathways of aromatic hydrocarbons, we found that most microbes only perform one single metabolic step (toluene: 80.3 %, Figure 7E; biphenyl: 86.6 %, Figure 7G; naphthalene: 72.9 %, Figure 7H).…”
Section: Species Exhibiting Metabolic Versatility While Being Non-aut...supporting
confidence: 91%
See 2 more Smart Citations
“…In contrast, most microbes lack a complete set of enzymes. Instead, many microbes contain a subset for hydrocarbon degradation, an observation that is in agreement with findings in several previous studies [21][22][23][24] , suggesting that MDOL is prevalent in hydrocarbon degradation. When we assessed three degrading pathways of aromatic hydrocarbons, we found that most microbes only perform one single metabolic step (toluene: 80.3 %, Figure 7E; biphenyl: 86.6 %, Figure 7G; naphthalene: 72.9 %, Figure 7H).…”
Section: Species Exhibiting Metabolic Versatility While Being Non-aut...supporting
confidence: 91%
“…We divided these pathways into several steps according to the following two conditions: (1) whether the selected intermediates are chemically stable and (2) whether the intermediates can be transported across the cell membrane so that be exchanged among different populations (Figure S13). To identify the distribution of the genes encoding the enzymes responsible for every metabolic step in microbial genomes, we searched for the hydrocarbon degradation genes in a database recently built from 24,692 publicly available archaeal (n = 1246) and bacterial (n = 23,446) genomes 21 . Based on these analyses, we classified these microorganisms into different genotypes that can perform one or multiple metabolic steps, which are conceptualized by bit strings containing "0", "1", "A" and "B" (Figure 7; Methods).…”
Section: Species Exhibiting Metabolic Versatility While Being Non-aut...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, AAI and ANI comparisons revealed that Pseudomonadales and Halieaceae populations that were only detected in EDB or SL mats were affiliated with different putative genera depending on the mats. These lineages, frequently identified as hydrocarbon degraders in contaminated aerobic systems, were found to degrade a large variety of petroleum compounds in marine biomes. ,, Therefore, this contrast between EDB and SL populations, which was not detectable by 16S rRNA and functional gene sequencing, suggests a fine selection of the Pseudomonadales and Halieaceae populations by the hydrocarbon content, leading to the growth of populations with similar gene content ( alkB and/or CYP153) but distinct substrate affinity. Together our results suggest that the detection of hydrocarbon degradation genes could not differentiate chronic to punctual hydrocarbon contamination and that an in-depth analysis of the microbiome combined with transcriptomic data are required to identify indicators of long-term hydrocarbon pollution in microbial mat ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria of the genera Pseudomonas and Sphingomonas were also detected during metagenomic analysis of samples of ground soils and seawater, sea ice, and crude oil encapsulating the sea ice of the Arctic region [ 28 , 29 ]. The use of n -alkanes and other petroleum components has been shown for members of the genera Pseudomonas , Rhodococcus , and Arthrobacter [ 30 , 31 , 32 , 33 , 34 ], whereas for bacteria of the genus Sphingomonas , this property is rare [ 35 , 36 , 37 , 38 ]. In order to determine how well the isolated four strains are adapted to the habitat conditions, the growth of the strains in oil at low temperatures (9 and −1.5 °C) was studied, and physiological and metabolic properties (temperature and salinity ranges for growth, the spectrum of enzymes, the substrates used, differences from type strains of respective species) were determined.…”
Section: Introductionmentioning
confidence: 99%